Understanding human brain function in real-world environments. - Feng Zhou; Benjamin Becker (PLoS Biology)
Functional MRI is invaluable in understanding brain function, but findings are often of limited real-world relevance. Neuroimaging in more naturalistic environments could reveal crucial insights into how the brain processes cognition, emotional experiences, and social interactions in daily life.